Exploratory Study: Design Capabilities Development for Malaysian Vendors in Automotive Industry - Ana Sakura, Zainal Abidin; Rosnah, Mohd Yusuff; Rasli, Muslimen (IEOM Research Solutions Pty Ltd, 2011)
The involvement of vendors in product development (PD) is able to make the process more efficient, effective and economical. Since vendors account for more than half of the total cost of production, their involvement have major influence on the cost and quality of the products. Vendors’ involvement in PD has significantly increased their importance; expose them to greater risks and challenges. As a return, the vendors are able to improve business performance results, productivity, and reputation, thus increasing the companies’ competitive advantage. To be successful in PD require certain level of design capabilities (DC), thus huge investment is needed. However, the Malaysian automotive market size is considered small and vendors’ capabilities are also limited. Since, studies on vendors’ DC, particularly, in Malaysia is very limited, an empirical study was conducted to explore on the critical success factors (CSFs) in enhancing the vendors design capabilities for the Malaysian automotive industry. A series of interviews were conducted on selected automaker and vendors from different categories to identify the critical success factors (CSFs) that are able to enhance the design capabilities development for Malaysian vendors.